El método BioAlberic: origen, desarrollo y aplicación en el control de los factores de riesgo cardiovascular - Ramírez López, Jesús A. (CorSalud, 2020)
El método BioAlberic: origen, desarrollo y aplicación en el control de los factores de riesgo cardiovascular